(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Patient safety is the prevention of errors that can cause harm to patients during treatment and care [7]. Internal safety is also an attribute of the medical industry, it minimizes incidents and maximizes recovery from incidents [5]. Objective: Analyze a number of factors related to the awareness of patient safety of nurses at the University of Medicine and Pharmacy Hospital, Hanoi National University in 2023. Method: Cross-sectional description, with analysis. Results: Reasonable arrangement of daily work plays the most important role in valuing patient safety (β= 0.595), followed by good department management and handling unsafe incidents good patients (β= 0.384 and 0.378) (p<0.001). Nurses who have worked in hospitals for <10 years have a higher rate of valuing patient safety and reporting patient safety incidents than nurses who have worked in hospitals for more than 10 years. 2,047 times (95% CI: 1,047-4,002), with a ratio of 59.6% compared to 41.9% (p<0.05) and 2.11 times (95% CI: 1,010-4,282), respectively with a ratio of 71.9% compared to 54.8% (p < 0.05). Nurses with errors in prescribing, recording, and dispensing drugs had a higher rate of valuing incident reporting and ward management to ensure patient safety than nurses without errors in prescribing. Recording and dispensing drugs were 2,116 times (95% CI: 1,032-4,338) with a rate of 55.8% compared to 37.4% (p<0.05) and 4,911 times (95% CI: 1,757), respectively -13,726) with a ratio of 50% compared to 41.7% (p < 0,05). Conclusion: The factors of reasonable daily work arrangement, working time, and errors in prescribing, recording, and dispensing medications by nurses are closely related to awareness of patient safety.